Journal Review: Potential of Gotu Kola Leaves (Centella asiatica) as Antibacterial Against Staphylococcus aureus: Jurnal Review: Potensi Daun Pegagan (Centella Asiatica) Sebagai Antibakteri Terhadap Staphylococcus aureus - Hafid Ernanda; Diniwati Mukhtar; Endang Purwaningsih; Jasir Hakim (Universitas Muhammadiyah Sidoarjo, 2025)
Herbal substances used worldwide include pegagan (Centella asiatica). Triterpenoids and saponins found in this plant have various medicinal benefits. Staphylococcus aureus has long been the most common cause of diseases present in society globally. The aimof this study is to outline the results of a literature review on the effectiveness of pegagan leaves (Centella asiatica). A literature review is the method used in this research. The selected journals are sourced from several national journal databases, resulting in 10 articles that meet the inclusion and exclusion criteria. The review findings indicate that pegagan leaves possess antibacterial activity against Staphylococcus aureus. Pegagan leaves have the potential to act as an antibacterial agent against Staphylococcus aureus with an effective extract concentration, specifically a high concentration of pegagan leaf extract.